Preparation of antioxidant peptides from Moringa oleifera leaves and their protection against oxidative damage in HepG2 cells - Tao, Liang; Gu, Fan; Liu, Yan; Yang, Min; Wu, Xing-Zhong; Sheng, Jun; Tian, Yang (Frontiers in Nutrition, 2022)
Moringa oleifera leaves are a kind of new food raw materials, rich in functional factors, Moringa oleifera leaves aqueous extract have antioxidant activity and Moringa oleifera leave protein is an important active ingredient in the aqueous extract. Numerous studies have shown that peptides have strong antioxidant activity.To reveal the antioxidant effects of Moringa oleifera (MO) leaves peptides, MO leave antioxidant peptides were isolated and prepared to clarify their antioxidant activity. MLPH1 (<1 kDa), MLPH3 (1 kDa ~3 kDa), MLPH5 (3 kDa ~5 kDa), and MLPH10 (5 kDa ~10 kDa) fractions were obtained by the membrane ultrafiltration classification of MO leaves proteolytic hydrolysate (MLPH). MLPH1 was further separated by centrifugal filters, and the fraction separated by less than 1 kDa (MLPH1-1) was identified and analyzed by LC–MS/MS. The purpose of this study was to investigate the effect of MO leaves antioxidant peptide pretreatment on H2O2-treated HepG2 cells and to refine the antioxidant activity. The results showed that MLPH1 had the strongest antioxidant activity, and three MO leaves antioxidant peptides (LALPVYN, LHIAALVFQ, and FHEEDDAKLF) were obtained. The peptide with the sequence LALPVYN and a molecular weight of 788.44 Da had the strongest antioxidant activity. After 24 h of LALPVYN pretreatment, the cell viability and the CAT, GSH-Px, and SOD enzyme activity were significantly increased, and the MDA, ROS, and apoptosis rates were significantly decreased. These results provide a theoretical basis for further research on the antioxidant mechanism of MO leaves peptides.